The architecture of hope : Maggie's cancer caring centres / Charles Jencks, Edwin Heathcote. - Jencks, Charles; Heathcote, Edwin (Frances Lincoln, 2010)
Jencks and Heathcote show the importance and hybrid quality of Maggie's cancer care centres. They look at how the need for these centres, which offer psychological, social and informational guidance, will inevitably grow in the future with an aging population. A visual history of one of Britain's most exciting contemporary building projects - Maggie's Centres; new cancer caring centres that offer a fresh approach in architecture and health, designed by world-renowned architects.